Spontaneous clearance of the human papilloma virus as a result of suppressive therapy with acyclic nucleosides of a recurrent herpes-viral infection - N I Tapilskaya; I N Vorobtsova; R I Glushakov (IP Berlin A.V., 2017)
Background. Genital human papillomavirus (HPV) infection is not effectively controlled and treated. Current dates suggest that 80% cases of HPV infections are transient and clear spontaneously, it is connected with the deterministic immune response. Results of several independent studies suggest that HSV-2 infections correlate with a higher than normal incidence of cervical cancer. Objectives. This study demonstrated a spontaneous clearance of the HPV follow the suppressive therapy of a recurrent HSV infection with acyclic nucleosides. Study design. We carried out a parallel observational study from 2015 to 2017. Herpes suppressive therapy with acyclic nucleosides (valacyclovir of 500 mg per day) during a 6 months is used to treat patients (n=32) aged 28 to 34 years (mean age 30.4±2.1 years) who have recurrent genital HSV infection and HPV infection both. The detection of HPV by RT-PCR before and after ant-herpetic therapy was investigated. Results. After treatment of HSV infection eradication of the one types of HPV was achieved in 43.75% cases, eradication of HPV-16 was achieved only in 15.4% (in 2 out of 13 patients) of cases, eradication HPV-18 was achieved in 25% (in 4 out of 16 patients) of cases. Decreasing of viral load occurred in 62.5% patients, full HPV-clearance was recorded in 15.6% of patients, but the high viral-load of HPV infection was preserved in 37.5% of the cases.